2021
DOI: 10.1080/14763141.2021.1875034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of back squat depth and load on lower body muscle activity in group exercise participants

Abstract: Les Mills BODYPUMP TM is a resistance training group exercise class with a low load, high repetition format. Squat training in BODYPUMP TM has two key variables: depth and load. The study aim was to determine the effect of these parameters on the mean and peak EMG amplitude of vastus lateralis, gluteus maximus, biceps femoris and lateral gastrocnemius. 10 female BODYPUMP TM participants (age 41 ± 9 years, height 161.9 ± 3.8 cm, mass 67.7 ± 7.0 kg) performed 1 x 7 squats under four conditions, representing ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…O'neil et al 20 observed that mean activity of vastus lateralis was 1.3-1.4-fold greater at 90° than at 125° for 23 BWL and 38 BWL. Peak activity was 1.8-1.9-fold greater at 90° of knee flexion.…”
Section: Electromiographic Activitymentioning
confidence: 98%
See 4 more Smart Citations
“…O'neil et al 20 observed that mean activity of vastus lateralis was 1.3-1.4-fold greater at 90° than at 125° for 23 BWL and 38 BWL. Peak activity was 1.8-1.9-fold greater at 90° of knee flexion.…”
Section: Electromiographic Activitymentioning
confidence: 98%
“…On further evaluation of full texts (ABC and FCS), 11 papers were excluded. Therefore, four studies 6,11,19,20 fulfilled all inclusion criteria and underwent critical appraisal.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations